Indeks Massa Tubuh Dan Obesitas Sentral Kaitannya Dengan Tekanan Darah Pada Anggota Batalyon X - Kusumarahmawati, Annisa; Bachtiar, Farahdina; Mailani, Rena; Sirada, Andy (Jurnal Fisioterapi Terapan Indonesia, 2023)
A sedentary lifestyle leading to obesity is one of the contributing factors to high blood pressure. Excessive fat can result in tissue dysfunction and is a key factor in the development of hypertension. Military personnel are expected to maintain good health and physical fitness. This study aimed to investigate the connection between Body Mass Index (BMI), central obesity, and blood pressure (BP) among Battalion X members. Methodology: A cross-sectional quantitative approach was employed with a sample size of 62 individuals. The data included height, weight, and waist circumference of the participants. Spearman's rho test was used for data analysis. The hypothesis testing indicated a significant relationship between BMI and central obesity with blood pressure, as demonstrated by p < 0.05. The correlation coefficients were as follows: BMI and systolic BP (r = 0.293), BMI and diastolic BP (r = 0.431), central obesity and systolic BP (r = 0.433), and central obesity and diastolic BP (r = 0.390). In sum, there is a significant relationship between BMI and central obesity and blood pressure in members of Battalion X.